The Effect of Exchange Rate and Tunneling Incentive on Transfer Pricing Decisions in The Property & Real Estate Sub-Sector on The IDX Period 2016-2023 - Azkia, Zahra Nurul; Pramayuda, Agung; Kusumawardhani, Aninditha Putri; Ningrum, Retno Widya (CV ODIS, 2025)
This study aims to find out the overview and influence of Exchange Rate and Tunneling Incentive on Tunneling Incentives. The object of this research is the Property & Real Estate sub-sector on the Indonesia Stock Exchange for the 2016-2023 period. The method used is a quantitative method with a descriptive and verifiable approach. The population in this study is 744 financial statements and annual reports from 93 companies in the Property & Real Estate sub-sector on the Indonesia Stock Exchange in the period 2016-2023, with a purposive sampling technique, so that the sample in this study amounted to 32 financial statements from 4 companies during the 2016-2023 period. The results of this study show that there is no influence on Transfer Pricing with a partial Exchange Rate of 0.2% and Tunneling Incentive has a partial on Transfer Pricing with an effect of 12.3%. Simultaneously, the results were obtained that the Exchange Rate and Tunneling Incentive had no effect on Transfer Pricing in Property & Real Estate Sub-Sector Companies on the Indonesia Stock Exchange for the 2016-2023 Period with an influence of 8.1%.